Fare teologia a partire dalla liturgia: Il dibattito tra O. Casel e K. Rahner - Caspani, Pierpaolo (La Scuola Cattolica, 2025)
The debate that in the early ’40s of the XX century opposes Rahner to Casel put forward the comparison between two different ways of practicing theology: ne that configures the access to the truth in terms of mystagogy, the other that consider absolutely necessary the appeal to a process logical and conceptual. In the conviction that such a comparison still maintains today its interest, the article reconstructs the debate between the two authors, verifying, in addition to the diversity of perspectives, the presence of common elements. In fact, in both cases, the faith has radically changed the shape of the practice with which the subject is delivered to the truth of God. Different, on the other hand, is the determination of that act: for Casel is the liturgical-sacramental action, while for Rahner is decisive the act with which, in fundamental experiences of life, the man is compared with itself, and he can thus come into contact with the mystery that lives in the “center more intimate” of his existence.